(untitled) (Journal of the College of Basic Education, 2022)
Poetry is distinguished by special expressive characteristics and techniques. If it depends on meter and rhyme, it always borrows part of its characteristics from the narration. Among these characteristics is the event, which constitutes a basic pillar of the narration elements, especially since poets often focus on the philosophy of the event more than the event itself. They meant to portray the event to the recipient more than to convey it, even if it is built in poetry on a scene that includes a group of clips that depend on brevity and condensation, and because of the limited space in the poetic text.